2023
DOI: 10.1002/smll.202307416
|View full text |Cite
|
Sign up to set email alerts
|

Title High Solar‐Thermal Conversion Aerogel for Efficient Atmospheric Water Harvesting

Xiangbing Wang,
Guofu Ma,
Shuzhen Cui
et al.

Abstract: The shortage of freshwater is a global problem, however, the gel that can be used for atmospheric water harvesting (AWH) in recent years studying, suffer from salt leakage, agglomeration, and slow water evaporation efficiency. Herein, a solar‐driven atmospheric water harvesting (SAWH) aerogel is prepared by UV polymerization and freeze‐drying technique, using poly(N‐isopropylacrylamide) (PNIPAm), hydroxypropyl cellulose (HPC), ethanolamine‐decorate LiCl (E‐LiCl) and polyaniline (PANI) as raw materials. The PNI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…These results further indicated that SCAC has good structural stability. The water absorption performance of SCAC was significantly superior to most of the reported hygroscopic materials (Figure f). , Furthermore, the water absorption rate of the hygroscopic agent was an indicator for judging the hygroscopicity. As can be seen from Table S2, the water absorption rate of SCAC was also much higher than that of the other hygroscopic agents in the Table.…”
Section: Resultsmentioning
confidence: 93%
“…These results further indicated that SCAC has good structural stability. The water absorption performance of SCAC was significantly superior to most of the reported hygroscopic materials (Figure f). , Furthermore, the water absorption rate of the hygroscopic agent was an indicator for judging the hygroscopicity. As can be seen from Table S2, the water absorption rate of SCAC was also much higher than that of the other hygroscopic agents in the Table.…”
Section: Resultsmentioning
confidence: 93%
“…Clearly, the optical absorption of C/PU/Al-fumarate across the entire wavelength range (200–2500 nm) was higher than that of PU/Al-fumarate (Figure d). This can be attributed to the black C particles coating the PU skeleton, which induces repeated reflection or scattering of light and absorbs internal light into C/PU/Al-fumarate. , Subsequently, the photothermal conversion efficiency of the samples under simulated solar radiation was demonstrated using an infrared thermography camera. Under one sun radiation intensity (100 mW cm –2 ), the maximum surface temperature of C/PU/Al-fumarate reached 72.1 °C (Figure e), which is significantly higher than that of PU/Al-fumarate (40.7 °C).…”
Section: Construction Of the Photothermal And Interfacial Coupling La...mentioning
confidence: 99%
“…Moreover, the AWH efficiency of such composites is usually increased with increasing the fraction of hygroscopic salts. ,, Due to the polyelectrolyte effect, however, quite a small amount of hygroscopic salt could be loaded into nonionic hydrogels or cellulose aerogels because an increase in the salt concentration decreased the osmotic pressure between the solution and the hydrophilic networks. The relatively low fraction of hygroscopic salt limits the moisture adsorption capacity and thus the efficiency for AWH. To enhance the hygroscopic salt fraction within composites, hydrophilic networks with porous structures have been developed for hygroscopic composite fabrication . For these composites, however, upon adsorption, the resulting salt aqueous solution tends to leak from the hydrogel because the hydrophilic networks cannot contain so much solution, again imposed by the polyelectrolyte effect.…”
Section: Introductionmentioning
confidence: 99%
“…To enhance the hygroscopic salt fraction within composites, hydrophilic networks with porous structures have been developed for hygroscopic composite fabrication. 29 For these composites, however, upon adsorption, the resulting salt aqueous solution tends to leak from the hydrogel because the hydrophilic networks cannot contain so much solution, again imposed by the polyelectrolyte effect.…”
Section: ■ Introductionmentioning
confidence: 99%